2020
DOI: 10.1002/onco.13534
|View full text |Cite
|
Sign up to set email alerts
|

Sex Representation in Clinical Trials Associated with FDA Cancer Drug Approvals Differs Between Solid and Hematologic Malignancies

Abstract: Background. Proportionate female representation in health research is necessary for scientific rigor and health equity. We aimed to assess the representation of women in clinical trials leading to U.S. Food and Drug Administration (FDA) cancer drug approvals. Materials and Methods. Trials supporting FDA cancer drug approvals between July 2008 and June 2018 were sourced from PubMed and ClinicalTrials.gov. The ratio of female to male trial enrollment was compared with cancer incidence and mortality in the U.S. u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…These included FDAAA801, 10 a federal act that required reporting of demographic enrollment data to ClinicalTrials.gov within 12 months of study completion, with monetary penalties of up to $10 000 per day and/or withholding of grant funds for noncompliance; the public release of these data on ClinicalTrials.gov 11 ; and updates to the Declaration of Helsinki that considered public registration of trials and disclosure of enrollee demographic characteristics obligatory research practices. 12 Little is known about disparities in enrollment and the effects of these policies on enrollment diversity for patients with acute myeloid leukemia (AML) 13 or acute lymphoblastic leukemia (ALL), rare but potentially curable blood cancers with numerous idiosyncratic care patterns that likely influence enrollment; these care patterns include the short time from diagnosis to therapy initiation, the inpatient setting of treatment, the high proportion of tertiary or quaternary care, and the historic paucity of effective treatments. 7,14 …”
Section: Introductionmentioning
confidence: 99%
“…These included FDAAA801, 10 a federal act that required reporting of demographic enrollment data to ClinicalTrials.gov within 12 months of study completion, with monetary penalties of up to $10 000 per day and/or withholding of grant funds for noncompliance; the public release of these data on ClinicalTrials.gov 11 ; and updates to the Declaration of Helsinki that considered public registration of trials and disclosure of enrollee demographic characteristics obligatory research practices. 12 Little is known about disparities in enrollment and the effects of these policies on enrollment diversity for patients with acute myeloid leukemia (AML) 13 or acute lymphoblastic leukemia (ALL), rare but potentially curable blood cancers with numerous idiosyncratic care patterns that likely influence enrollment; these care patterns include the short time from diagnosis to therapy initiation, the inpatient setting of treatment, the high proportion of tertiary or quaternary care, and the historic paucity of effective treatments. 7,14 …”
Section: Introductionmentioning
confidence: 99%
“…In our study, the female gender was more evenly distributed in patients with SGC compared to patients with RCC (55% vs, 16%, respectively) and this may partly explain the higher geometric mean cabozantinib C min levels observed in the SGC group. This potential gender effect warrants further research in larger cohorts as indications for cabozantinib are extending and females are often underrepresented in clinical trials 28 . Another possible explanation for the observed difference in cabozantinib concentrations in SGC and RCC patients may be the difference in serum albumin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This potential gender effect warrants further research in larger cohorts as indications for cabozantinib are extending and females are often underrepresented in clinical trials. 28 Another possible explanation for the observed difference in cabozantinib concentrations in SGC and RCC patients may be the difference in serum albumin concentrations. Previously, lower albumin concentrations have been associated with lower maximal cabozantinib concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, trial populations may not always represent the population that they are trying to emulate. It has been shown in several studies, in both oncology and nononcology clinical trial settings, that women may be underrepresented in clinical trials 10‐13 . Although some reports refute this claim and a plethora of barriers exist to clinical trial participation and enrollment, there are known differences in the clinical outcome of medications, such as adverse drug reactions, which may be missed in underrepresented trials 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the existence of racial and age disparities in oncology clinical trials, but are less robust in assessing gender variation 17,18 . Mendis et al recently showed a slight female underrepresentation in hematological trials and a significant underrepresentation in solid organ malignancies using the International Agency for Research on Cancer and odds ratios for female trial enrollment 13 . The purpose of this study was to further clarify whether there is truly a gender disparity in clinical trials leading to cancer drug approvals using US Food and Drug Administration (FDA)‐approved clinical trials from January 2014 to April 2019 by calculating enrollment incidence disparity (EID) using the National Cancer Institute (NCI) Surveillance, Epidemiology, and End Results (SEER) program database.…”
Section: Introductionmentioning
confidence: 99%